The Prince, the Noblemen and the Painter: Collectionso Works of Art in Copenhagen Between 1800 and 1848 - Christensen, Charlotte (Artium Quaestiones, 2023)
The history of collecting in Denmark and Norway in the 19th century is intimately connected with the history of the painters and sculptors active during that period. Only in Copenhagen were the Royal and private collections accessible to the artists, for whom copying paintings by Old Masters formed an important part of their curriculum. Major collectors of the Age were Prince Christian Frederik (later King Christian VIII of Denmark), who mainly acquired paintings and sculptures by contemporary artists, and the portrait painter Christian Albrecht Jensen, whose preference was to buy and sell the works of Old Masters. In Copenhagen, the collections of the Counts Moltke, which mainly consisted of works by Dutch painters, was open to the public, while the Royal Collection (today a part of Statens Museum for Kunst) could only be visited from 1827 onwards. None of the three collections dealt with in the present article have survived until today, while the works of art and the antiques belonging to the sculptor Bertel Thorvaldsen are at present housed in the museum bearing his name.